MODEL PERTUMBUHAN POHON JATI (Tectona grandis L.f.) DI KPHP BATULANTEH, SUMBAWA, NTB - Woesono, Hastanto Bowo; Suhartati, Tatik; Pujasa, Dwita (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2019)
Teak is a high value wood. The tree trunk has a high economic value because it provides multipurpose wood products. Tree trunks have distinctive biometric characteristics, including teak trunks. The biometric characteristic of a tree species is a problem in the science of forest planning, because the growth of tree trunks is influenced by many factors, including differences in age, location and site. This research will be arranged biometric model of teak tree that grows in Batulanteh Forest Management Unit, beginning with collecting physical data of tree through measurement of tree dimension. This study uses 75 sample trees grown in the Batulanteh Forest Management Unit area. The data used were tested outlier with boxplot method and calculated ratio and correlation. The regression equation was done by using SPSS version 23 program. Different ratios between tree dimensions at different ages were tested using complete randomized design. The results of this study indicate that the growth model of base diameter, diameter at breast height, and total height are characteristic of trees that are highly correlated with other tree biometrics characteristics. So in the management of teak forests Batulanteh Forest Management Unit can make these three characteristics as a reference in looking at the characteristics of other trees. The results also show the ratio Dp / Dbh, Tt / Dbh still fluctuate throughout the age of 10 to 22 years. Keywords : Teak, growth model, inter-dimensional ratio, age